2009
DOI: 10.1002/adma.200801668
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State Supramolecular Organization of Polythiophene Chains Containing Thienothiophene Units

Abstract: We use molecular modeling and the simulation of X‐ray diffraction patterns to determine the molecular packing of a thiophene‐based polymer showing exceptionally high field‐effect mobilities (up to 1 cm2 V−1 s−1). We focus on the organization of the polymer chains in lamellae and the orientation of these crystalline domains with respect to the substrate in thin films. The analysis is supported by XRD and NEXAFS experiments and is complemented by calculating intermolecular transfer integrals, which govern the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
106
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(119 citation statements)
references
References 24 publications
10
106
3
Order By: Relevance
“…Simulations of the two polymer melts show that the structural properties in PBTTT facilitate both intraand inter-chain charge transport compared with P3HT, due to greater degree of planarity, closer and more parallel stacking of the thiophene and thienothiophene rings, and possible interdigitation of the dodecyl side chains. X-ray diffraction studies have shown that PBTTT indeed forms interdigitated alkyl side chains (Brocorens et al, 2009;Kline et al, 2007). Thus, the crucial role played by the bulky dodecyl side chain and thienothiophene ring, respectively, in determining intra-chain and inter-chain structural order is clarified through these simulations .…”
Section: Atomistic Structure and Dynamics Of Polythiophene Semiconducmentioning
confidence: 96%
“…Simulations of the two polymer melts show that the structural properties in PBTTT facilitate both intraand inter-chain charge transport compared with P3HT, due to greater degree of planarity, closer and more parallel stacking of the thiophene and thienothiophene rings, and possible interdigitation of the dodecyl side chains. X-ray diffraction studies have shown that PBTTT indeed forms interdigitated alkyl side chains (Brocorens et al, 2009;Kline et al, 2007). Thus, the crucial role played by the bulky dodecyl side chain and thienothiophene ring, respectively, in determining intra-chain and inter-chain structural order is clarified through these simulations .…”
Section: Atomistic Structure and Dynamics Of Polythiophene Semiconducmentioning
confidence: 96%
“…This explains why the density does not change much from NI to I (1.2 versus 1.3). NI is much less stable than I, by 14.7 kcal mol À1 per monomer unit [65]. PBTTT is therefore expected to be interdigitated (see middle of Figure 1.7).…”
Section: Polythiophene Derivativesmentioning
confidence: 99%
“…An original approach validating the use of force field calculations via the simulation of corresponding X-ray diffraction patterns is also introduced here (see Ref. [65] for the original reference).…”
Section: Polythiophene Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-organization of π-conjugated units also affects the electronic properties of organo-gels [12][13][14][15] and conductive polymers. [16][17][18] Unlike organic crystals and amorphous solids, supramolecular structures can be constructed in liquid crystal phases using nanosegregation between immiscible moieties built into LC molecules. 19 Kato and coworkers reported one-and two-dimensional ionic conduction in nanosegregated supramolecular liquid crystals.…”
Section: Introductionmentioning
confidence: 99%